Pengaruh Persepsi Orang Tua terhadap Pembelajaran CALISTUNG dI TK ASIH - Sely Nurhalimah; Eva Gustiana (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2021)
Parents' Perception. Parents' Perceptions of Calistung Learning for Early Childhoods at TK Asih, Cibeureum District, Kuningan Regency. The problem in this study arises from the perception of the parents themselves wanting their children to be good at reading, writing and arithmetic when their children have graduated from the institution. Calistung is indeed a phenomenon in itself, now it is becoming increasingly hotly discussed by parents who have kindergarten age children because they are worried that their children will not be able to attend lessons at their school later if they have not been equipped with Calistung skills from the start. Parents' concerns are even more intense when their children cannot read before entering elementary school. The purpose of this study was to obtain information about the influence of parents' perceptions on Calistung. This research is a quantitative research. The subjects of this study were parents whose children went to TK Asih, which is located in Sukarapih Village. The calculation that the researcher did was to use IBM SPSS Statistics 20 and calculate the results of the information he had obtained using a simple linear regression test with pre-requisites for normality and linearity tests. The researcher conducted his research with 31 parents of students whose children were already in class B. The instrument in this study used a questionnaire. The results of this study indicate that the perceptions of each parent are different. Through the linear regression test, the regression equation Y = 21.909 - 0.235X is obtained. The conclusion of this study is that there is no effect of parental perceptions on children's learning. Keywords: Parents' Perception, Calistung